2021
DOI: 10.1097/md.0000000000026741
|View full text |Cite
|
Sign up to set email alerts
|

Stroop effect in smartphone addiction among college students

Abstract: Smartphone addiction (SPA) affects an increasing number of college students, but it remains poorly understood. This study aimed to explore the psychological mechanism of the decrease in cognitive control ability from cognitive psychology in students with SPA.The smartphone addition tendency scale (MPATS) was used to identify 64 undergraduates with SPA (MPATS > 45) and 64 sex- and age-matched controls (MPATS < 30).The 2 groups were well matched for age and sex distribution. The RT of the SPA group under the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…Therefore, extraverts are more likely to become addicted to smart phones. We found an inverse correlation between SPAT and neuroticism, which is inconsistent with other reports in the literature 23,24 and needs further exploration.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, extraverts are more likely to become addicted to smart phones. We found an inverse correlation between SPAT and neuroticism, which is inconsistent with other reports in the literature 23,24 and needs further exploration.…”
Section: Discussioncontrasting
confidence: 99%
“…Numerous investigations have demonstrated that MPA negatively affects mental health by causing anxiety [ 10 ] and depression [ 11 , 12 ], affecting sleep quality [ 13 - 15 ] and cognitive function [ 16 ], and causing muscle pain [ 17 , 18 ], thereby affecting work productivity and the quality of life of individuals. Thus, MPA is now considered an important worldwide public health topic [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some other studies focus on academic adaptability and learning burnout (27,64), self-efficacy and academic adaptability (41,79,80) and selfefficacy and learning burnout (26,69). The correlation between smartphone dependence and learning burnout among university students have also been highlighted (28,29,81). Some researches have analyzed the moderating variables between the two.…”
Section: Research Value 51 Contributionsmentioning
confidence: 99%
“…There is a positive relationship between smartphone dependence and learning burnout ( 28 ). Zhang et al ( 29 ) find that the higher the level of smartphone dependence, the less will power students have to resist and control the temptation of smartphones, the slower they respond to the teacher, and the more likely they are to fall into learning burnout, such as lack of interest in academic life, lethargy, avoidance, and even indifference. Related studies have shown that smartphone dependence is positively correlated with learning burnout.…”
Section: Introductionmentioning
confidence: 99%